Nag Hammadi and Related Literature - McGuire, Anne (The Oxford handbook of New Testament, gender, and sexuality, 2019)
This essay examines the imagery of gender and sexuality in four documents from the Nag Hammadi library. The selected works share a religious emphasis on the saving power of religious knowledge or gnōsis, but represent distinct literary genres and differing religious perspectives on gender, sexuality, and divine–human relations. The essay analyzes each text’s uses of gender imagery in literary context and in relation to key religious ideas, such as the relation of the divine and human; social relations between individuals or groups; and the experiential domain of ritual, religious experience, and/or sexual relations. It also considers the ways these four texts illustrate some of the distinctive ways in which Nag Hammadi literature employs the imagery of gender and sexuality to articulate distinctive conceptions of difference and to engender salvation among their knowing readers and hearers.